Assessing the effectiveness of climatic information services in reducing disaster loss and damage among marginal farmers - Md. Faisal; Tahura Yeasmin; Milton Kumar Saha; Tanvir Ahmed (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: Climate change poses significant challenges to agricultural livelihoods in coastal Bangladesh, particularly for marginal farmers who are highly vulnerable to cyclones, salinity intrusion, irregular rainfall, and rising temperatures. This study assessed the effectiveness of climatic information services (CIS) in minimizing agricultural loss and damage among marginal farmers in Srirampur Union of Dumki Upazila, Patuakhali District, Bangladesh. Methods: A mixed-method approach was adopted using both primary and secondary data. Primary data were collected through structured questionnaire interviews with 100 marginal farmers selected through purposive sampling, while secondary data were obtained from relevant literature and published sources. Findings: The findings reveal that all respondents observed changes in weather patterns, only 12% were aware of climate change, and only 14% were aware of climatic information services. The study further found that 40% of respondents considered CIS inaccessible, while 60% reported that climatic information was unclear and difficult to understand. Only 8% of farmers fully relied on climatic information for farming decisions, and 32% reported changing farming practices based on climatic information. Furthermore, 95% of respondents experienced crop failure or yield losses due to climatic factors, while 53% perceived climatic information services as ineffective in minimizing loss and damage. The study identified major barriers to the effective utilization of CIS, including low awareness, poor digital access, lack of institutional support, inadequate training, and limited confidence in the reliability of climatic information. Conclusion: Based on these findings, the study recommends improving awareness programs, strengthening digital and institutional support systems, enhancing climate education, and developing farmer-friendly climatic information delivery mechanisms. Novelty/Originality of this article: This study provides empirical evidence that, despite widespread exposure to climate-related hazards, the utilization and perceived effectiveness of climatic information services among marginal farmers in Coastal Bangladesh remain low because of limited awareness, poor accessibility, inadequate institutional support, and low digital connectivity. The findings identify critical barriers that should be addressed to improve climate information delivery and strengthen farmers' adaptive capacity and resilience.